2021
DOI: 10.3389/fmicb.2021.646567
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Complete Mitochondrial Genome of Basidiomycete Yeast Hannaella oryzae: Intron Evolution, Gene Rearrangement, and Its Phylogeny

Abstract: In this study, the mitogenome of Hannaella oryzae was sequenced by next-generation sequencing (NGS) and successfully assembled. The H. oryzae mitogenome comprised circular DNA molecules with a total size of 26,444 bp. We found that the mitogenome of H. oryzae partially deleted the tRNA gene transferring cysteine. Comparative mitogenomic analyses showed that intronic regions were the main factors contributing to the size variations of mitogenomes in Tremellales. Introns of the cox1 gene in Tremellales species w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…As mobile genetic elements in fungal mitogenome, intron dynamics play an important role in altering organization or size of fungal mitogenomes ( Himmelstrand et al, 2014 ; Gomes et al, 2018 ; Fan et al, 2019 ; Li et al, 2021a ). In the present study, we found the number and class of basidiomycete introns varied greatly, even between closely related basidiomycete species, and a significant correlation between the mitogenome size and intron number of 79 basidiomycetes were detected.…”
Section: Discussionmentioning
confidence: 99%
“…As mobile genetic elements in fungal mitogenome, intron dynamics play an important role in altering organization or size of fungal mitogenomes ( Himmelstrand et al, 2014 ; Gomes et al, 2018 ; Fan et al, 2019 ; Li et al, 2021a ). In the present study, we found the number and class of basidiomycete introns varied greatly, even between closely related basidiomycete species, and a significant correlation between the mitogenome size and intron number of 79 basidiomycetes were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Intron dynamics play an important role in altering organization and size of fungal mitogenomes (Himmelstrand et al, 2014;Li et al, 2021). Group I and group II introns are commonly found, among other places, in organelles of higher eukaryotes (Haugen et al, 2005).…”
Section: Introns and Accessory Mitochondrial Genesmentioning
confidence: 99%
“… 2018 ; Li, Li, et al. 2021 ). Briefly, the protein-coding genes, rRNA genes, tRNA genes, and introns of the M. bursus mitochondrial genome were annotated using MITOS (Bernt et al.…”
mentioning
confidence: 99%